Smart Atm Cardholders’ Attitude And Usage Level - A Study Of Sungai Petani Residents - Kumegan, Karuna (2004)
Smart card technology has experienced tremendous growth on the global basis in the application of various sectors such as transportation, health, telecommunication, insurance, financial industry and etc. It has changed the way the world doing business and consumer make purchasers on a daily basis. Smart card has been designed to become the future method of payment and information storage system. It has been utilized excessively during the last couple of decades. It provides better security, intelligence, speed and convenience.